Quantitative Reconstruction of Precipitation and Lake Areas During Early to Middle Holocene in Mu Us Desert, North China - Li, Dawei; Wu, Yongqiu; Tan, Lihua; Wen, Yanglei; Fu, Tianyang (Frontiers in Earth Science, 2022)
Paleoclimatic researches have revealed that the East Asian summer monsoon (EASM) has strengthened and precipitation increased in north China during the early to middle Holocene. The lacustrine landform and sediment recorded approximately simultaneous Holocene high lake levels. However, relatively few studies have been reported involving the quantitative reconstruction of precipitation and lake areas in the Mu Us Desert (MUD), northwest edge area of the modern EASM. Based on the lacustrine landform, and by using the lake hydrologic model, this study quantitatively reconstructed precipitation and lake areas during the early to middle Holocene in the MUD. The results revealed the following: (1) A total of 127 paleolakes existed in the closed drainage area during the early to middle Holocene. The area of paleolakes was 896.1km2, which is 2.96 times that of modern lakes. The relative height between the highstand and the modern lake surface is ~5–9 m. (2) Precipitation during the early to middle Holocene decreased from 550 mm in the southeast to 350 mm in the northwest. The 400 mm isohyet moved 130–170 km to the northwest, roughly coincident with the modern 250 mm isohyet. (3) The relative increase in precipitation was ~32–60%, and the increase in the west was significantly higher than in the east. The precipitation gradient in much of the MUD was lower than the present. The results show that the monsoon edge area and monsoon rain belt migrated to the northwest during the early to middle Holocene. The MUD was stably dominated by the EASM. Data also showed that the spatio-temporal pattern of the climate during the early to middle Holocene was relatively humid with a decreased precipitation gradient for millennia.